Talanoa: Matala 'Oe Fonua - Toluta'u, Talita (Auckland University of Technology, 2008)
This study is concerned with representation. It considers the nature of a culturally located narrative form called talanoa and its creative translation into film. The film Talanoa: Matala ‘o e Fonua that constitutes the designed outcome of this project considers the memories of three Tongan women who left their homeland to settle in New Zealand between 1970’s and 1990’s. It is designed as three related garlands that exist as a related unit. Talanoa: Matala ‘o e Fonua is therefore, a creative synthesis of their talanoa, into a new form of documentary that is designed to capture the cultural and emotional resonance of their stories. The work orchestrates photography, animation, sound design, filmed footage and extensive postproduction research into a unique text that seeks to move the parameters of documentary beyond the visual interview. In doing so, the research draws heavily on Tongan paradigms of narrative and representation.
Keywords: Graphic design; Tongan women; Immigrant experience; Kalaka; Pacific research; Documentary making